Effect of extreme pressure agents on the anti-scratch behaviour of high-speed steel material. (January 2015) - Hao, Liang; Jiang, Zhengyi; Wei, Dongbin; Zhao, Yue; Zhao, Jingwei; Luo, Ming; Ma, Li; Luo, Suzhen; Jiang, Laizhu
Abstract: Extreme pressure (EP) additives form reasonable hard films by reacting with metal surfaces and are a good alternative to protect the surface of metals exposed to various types of wear. In this paper, the chemical reactions between high-speed steel (HSS) roll material and various EP agents, such as those containing sulfur, chlorine and zinc dialkyl dithio phosphate (ZDDP), were investigated by dropping EP solutions on the heated HSS samples. The research results show that the sulfur element from the sulfur EP solutions was found in the substrate and the carbides. However, the chromium element could not be detected in the sample, and the decomposition products of the ZDDP covered the sample. The scratch tests were carried out to demonstrate that the ZDDP is more resistant to scratching than other EP agents. Highlights: Carbides in HSS are less oxidized than matrix. S type EP agents can react with HSS material, while Cl type cannot react. Decomposition products of ZDDP cover the HSS substrate. ZDDP shows the strongest capacity of anti-scratch among all tests cases.